2021
DOI: 10.1038/s41380-021-01339-z
|View full text |Cite
|
Sign up to set email alerts
|

Multi-omics of human plasma reveals molecular features of dysregulated inflammation and accelerated aging in schizophrenia

Abstract: Schizophrenia is a devastating psychiatric illness that detrimentally affects a significant portion of the worldwide population. Aging of schizophrenia patients is associated with reduced longevity, but the potential biological factors associated with aging in this population have not yet been investigated in a global manner. To address this gap in knowledge, the present study assesses proteomics and metabolomics profiles in the plasma of subjects afflicted with schizophrenia compared to non-psychiatric contro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
29
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 40 publications
(30 citation statements)
references
References 60 publications
1
29
0
Order By: Relevance
“…The metabolic profile of SZ showed accelerated ageing and inflammatory response. These data are supported by proteomic studies ( Campeau et al 2022 ). An experimental study examined the metabolic profiles of chronically hospitalised SZ candidates and showed lower glutamate and urea cycle metabolism (Okamoto et al 2021 ).…”
Section: Metabolomics Features In Schizophreniasupporting
confidence: 66%
“…The metabolic profile of SZ showed accelerated ageing and inflammatory response. These data are supported by proteomic studies ( Campeau et al 2022 ). An experimental study examined the metabolic profiles of chronically hospitalised SZ candidates and showed lower glutamate and urea cycle metabolism (Okamoto et al 2021 ).…”
Section: Metabolomics Features In Schizophreniasupporting
confidence: 66%
“…This integrative approach may also interpret new connections between tissue types, including relationships between CSF and blood lipid levels, not seen by chance or simple associations, leading to the discovery of new biomarkers and therapeutics. Although the integration of lipidomics datasets is still in its infancy, some of the analyses reported here have applied integrative strategies and demonstrated new functional relationships of lipids with proteins, metabolic pathways, and gene expression, previously unknown in psychiatric conditions ( 78 , 100 , 102 ).…”
Section: Discussionmentioning
confidence: 99%
“…In a recent study, Campeau et al . ( 100 ) performed a multi-omics analysis of plasma samples from individuals with SCZ and healthy controls (aged 28–74 years) to examine age- and disease-related effects on various proteins and metabolites. The majority of altered metabolites between SCZ and healthy controls were classified as lipids.…”
Section: Lipidomics Investigations Into Ssd and Psychosis Fluid Bioma...mentioning
confidence: 99%
“…Fifty micrograms of peptide was dried down and labeled using TMT10plex Isobaric Labeling reagents (catalog #90406) as described in Campeau et al. 49 Labeled peptides were subsequently dried down, desalted, and fractionated using high pH reverse phase fractionation (Thermo Ultimate 3000 HPLC off-line fraction collector and c18 column, 37 s per well, 96 wells total). After fractionation samples were concatenated into 24 samples.…”
Section: Methodsmentioning
confidence: 99%